Purificação parcial e caracterização de uma amilase estável de Fusarium solani e potencial aplicação na indústria - LIMA, Fernanda Jeniffer Lindoso (2023)
Amylases are carbohydrases widely distributed in nature and can be found in animals, plants and microorganisms. Amylase is mainly used in the pharmaceutical industry as a digestive aid, debridement, wound healing and anti-cancer therapy. Filamentous fungi of the Fusarium solani species complex are good producers of extracellular enzymes. The objective of this work was to evaluate a partially purified fraction of Fusarium solani as a source of carbohydrate biocatalyst enzymes for use in the industry. After PCR and electrophoresis, the molecular identification was confirmed with the 560 bp pattern for the fungus Fusarium solani. The crude extract obtained from the submerged fermentation of Fusarium solani using 6% starch was subjected to partial purification carried out with ammonium sulfate in two fractions with different degrees of saturation: F1(0-40%) and F2 (40-80%). Partially purified F2 amylase exhibited specific activity of 4603 U/mg protein. After observing the high amylolytic activity in this fraction in relation, the physicochemical characterization of the amylases was carried out. The optimum pH and temperature for enzymatic activity were 4.5 and 95°C, respectively. It was found that the thermal stability of the enzyme was maintained after 1 h. The F2 amylolytic activity of Fusarium solani de was inhibited in the presence of the elements Fe 3+ , Na + , Ca 2+, Mn 2+, Cu 2+, Cl - , Zn 2+, K+ at concentrations of 5 and 10 mM. The purified enzyme showed remarkable stability in relation to surfactants (Triton X-100, Tween 20, Tween 80 and SDS). In the presence of EDTA the amylolytic activity of F2 amylases was slightly increased, suggesting that this enzyme has a weak interaction with the chelating reagent. Extremophilic amylase was stable in the presence of various organic solvents such as methanol, isopropanol, ethanol and acetone. These properties indicate potential biotechnological applications of this enzyme in industry, with ecologically correct production.